Restored Activation of Primary Motor Area from Motor Reorganization and Improved Motor Function after Brain Tumor Resection - Shinoura, N.; Suzuki, Y.; Yamada, R.; Kodama, T.; Takahashi, M.; Yagi, K. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Reorganization of brain function may result in preservation of motor function in patients with brain tumors. The goal of the present study was to investigate whether function of the primary motor area (M1) was restored and whether motor function improved after brain tumor resection.METHODS: Five patients with metastatic brain tumors located within or near M1 underwent awake surgery with intraoperative cortical mapping and continuous task monitoring. Preoperative and postoperative functional MR imaging (fMRI) was performed during hand clenching, and diffusion tensor imaging (DTI) was performed in 1 case to further characterize the area activated in fMRI.RESULTS: Preoperative fMRI performed during hand clenching demonstrated reorganization of motor function. In patients with severe paresis (cases 3, 4, and 5), clenching of the affected hand induced a large blood oxygen level–dependent response in the right hemisphere, mainly in the anterior temporal lobe, despite the location site of the tumor. Postoperative fMRI during hand clenching demonstrated activation of the contralateral M1. Furthermore, in case 5, DTI detected tracts, possibly the inferior longitudinal fasciculus, arising from anterior temporal activated area as well as tracts connecting the premotor and M1 activated area. This patient demonstrated mirror movement of the hand during the course of motor function recovery.CONCLUSIONS: Tumor resection resulted in restoration of M1 function and improved motor function in patients with preoperative reorganization of M1 function. Furthermore, the preoperative reorganization of motor function in cases with severe paresis may be related to changes in the right hemisphere, including the temporal lobe.